Cashier Application on an Android Smartphone to Support Transaction Management in Small Scale Business - Heru Supriyono; Diana Gusti Ambarwati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Customer service time is very important for UD. Hardi Drum which is a small-scale business in the field of selling used drums. Service to customers which is still manual, writing transaction data on notes takes time especially if the transactions volume is large. The purpose of this article is to introduce a cashier application system that can be run on Android smartphones. The introduced cashier application has various menus such as managing goods/stock data, inventory, transaction services, and recording sales results. The shopping receipts generated by the cashier application can be printed on a portable printer directly or can be saved in the form of a pdf file. All transaction data is automatically recapitulated by the cashier application which can be displayed at a certain time range that can be selected with the search menu. After being trained starting from the installation process on smartphones and the operation of all existing features and menus, owners and employees at UD. Hardi Drum were asked to evaluate the level of usability of the application by answering a questionnaire. The calculation results of the questionnaire showed that the application has a usability value of 71.8 which means that the application was accepted at a good level. The introduced cashier application has the potential to increase service time efficiency.